KARAKTERISTIK MUTU BAKSO JAMUR SAWIT DENGAN VARIASI KONSENTRASI JAMUR SAWIT (Volvariella volvacea) DAN TEPUNG MOCAF (Modified cassava flour) - Rosianti, Elpera; Arif, Hilda Meisya; Prasetya, Andwini (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
The purpose of this study is to characterize the physical, chemical, organoleptic properties, and analyze the advantages of palm mushroom meatballs. This study used a Complete Random Design (RAL) with 5 treatments, namely the comparison of the composition of palm mushrooms and mocaf flour 30%: 70%, 40%: 60%, 50%: 50%, 60%: 40%, 70%: 30%. The results showed that the average yield of palm mushroom meatballs was between 54% and 82.26%. The average texture of palm meatballs is highest in the treatment of the composition of palm mushrooms and mocaf flour 30%: 70% with a texture value of 26 mm. The higher the composition of palm mushrooms, the more textured the meatballs tend to be softer or less chewy. The average moisture content of palm meatballs was the lowest in the treatment of the composition of palm mushrooms and mocaf flour 60%: 40%, which was 9.80%. The average protein content of palm mushroom meatballs was the highest in the treatment of the composition of palm mushrooms and mocaf flour 70%: 30%, which was 16.58%. The higher the composition of palm mushrooms, the higher the protein content of palm mushroom meatballs. The average fiber content of palm mushroom meatballs is the highest in the composition of palm mushrooms and mocaf flour 70%: 30%. The average fat content of palm mushroom meatballs is the highest, which is 70%: 30%. Based on organoleptic analysis, palm mushroom meatballs with a composition of palm mushrooms and mocaf flour 60%: 40% gave the highest assessment, namely in terms of color 3.60 (like), taste 3.85 (like), and texture 3.90 (like). From the results of the analysis of the profit obtained in one month of production amounted to Rp.6,327,500.